Rancang Bangun Purwarupa Alat Pengayun Ranjang Bayi Menggunakan Sensor Suara Berbasis Mikrokontroler Atmega328 - Antonius Son Gelu; Yoga Listi Prambodo; Mega Tri Kurnia (Sistem Komputer & Teknologi Intelegensi Artifisial (SIKOMTIA), 2023)
Baby cribs typically require human effort to swing, which can be time-consuming and exhausting if done manually by a person continuously. Hence, the idea emerged to design a prototype device that can automatically swing the baby crib, helping to ease the mother's task, just like cradling a baby. The purpose of this prototype device is to lighten the burden of mothers who often become fatigued when soothing their children and then need to leave them in a calm state to attend other activities. This device can automatically swing the crib triggered by the sound of a crying baby, which will be detected by a sound sensor and processed by the ATmega328 microcontroller on Arduino. Subsequently, Arduino commands the servo motor to activate and swing the baby crib. Having this device will provide benefits in assisting a mother to soothe her baby while still being able to carry out other activities.